2019
DOI: 10.3390/su11133523
|View full text |Cite
|
Sign up to set email alerts
|

Life Cycle Assessment of Seabass (Dicentrarchus labrax) Produced in Offshore Fish Farms: Variability and Multiple Regression Analysis

Abstract: Equations were developed through multiple regression analysis (MRA) to explain the variability of potential environmental impacts (PEIs) estimated by life cycle assessment (LCA). The case studied refers to the production of seabass in basic offshore fish farms. Contribution analysis showed that the components of the system which most influence the potential environmental impacts are the feed (54% of the overall impact) and the fuel consumed by vessels operating in the farm (23%). Feed and fuel varied widely fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 55 publications
1
11
1
Order By: Relevance
“…Aubin et al [24] reported an FCR of 1.77 for sea bass rearing in Greece, while a Tunisian study reported an FCR of 1.85 and 1.88 for sea bream and sea bass, respectively [27]. Garcia et al [26] reported an FCR of 2 for sea bream production in Spain and, more recently, Garcia et al [25] reported an FCR of 1.5 to 1.9 for sea bass, depending on the growing stage. As the FCR depends on a series of environmental factors, those variations amongst studies are reasonable.…”
Section: Sea Bass and Sea Bream Rearing Inventoriesmentioning
confidence: 99%
See 4 more Smart Citations
“…Aubin et al [24] reported an FCR of 1.77 for sea bass rearing in Greece, while a Tunisian study reported an FCR of 1.85 and 1.88 for sea bream and sea bass, respectively [27]. Garcia et al [26] reported an FCR of 2 for sea bream production in Spain and, more recently, Garcia et al [25] reported an FCR of 1.5 to 1.9 for sea bass, depending on the growing stage. As the FCR depends on a series of environmental factors, those variations amongst studies are reasonable.…”
Section: Sea Bass and Sea Bream Rearing Inventoriesmentioning
confidence: 99%
“…The hatching and nursing phase includes activities taking place in onshore facilities, stock maintenance and phytoplankton and zooplankton production. Given the nature of the operations and that the fish is transferred to the rearing facility when it reaches a mass of 2 g, it is reasonable to assume that the environmental impacts of the hatching and nursing phase are insignificant compared to the rearing operation, growing fish from 2 g to 600 g. Therefore, it was excluded from the product system, in line with preceding literature studies [25,26]. This assumption is further supported by the fact that a previous study focusing on rainbow trout production reported a negligible contribution of the hatchery to the life cycle climate impact and a 2% contribution to the eutrophication impact [37].…”
Section: Inventory Analysismentioning
confidence: 99%
See 3 more Smart Citations